Spectrum aware self-organizing networking in OFDMA / LTE heterogeneous networks - Karaman, Melih Ahmet. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2012., 2012)
Emerging information technologies provide a large number of services which require high throughput for the users. In order to supply the data rate needed by the consumer, the evolving ecosystem of mobile technologies have been shifting from coverage to capacity era. Needs of higher capacity can be achieved by small cell approach that provides good indoor coverage for video and high speed data services. Whilst Cellular Network Architecture is shifting from Circuit-Switched mode to Packet-Switched mode, small cells have begun to adapt this evolution earlier since they use the largest packet network, \the Internet", as a backhaul, that is why they perfectly t in the packet oriented architecture and they are inevitable in Long Term Evolution (LTE). Deployment of small cells requires exible and dynamic operation, administration, maintenance and provisioning schemes. Self-organization and self-optimization of network elements emerge as a necessity for network management. Hence, using Self-Organizing Networks (SON) algorithms and techniques in LTE small cells is a key issue; in this study we are going to discuss the impact of SON in performance of LTE small cells after reviewing the principles of the topic.
Keywords: Long-Term Evolution (Telecommunications); Self-organizing systems.